The sublethal effects of neonicotinoids on spiders are independent of their nutritional status - Milan Řezáč (Nature Portfolio, 2021)
Abstract Spiders were recently shown to be adversely affected by field-realistic concentrations of a broad scale of neonicotinoid insecticides. Among the reported effects of neonicotinoids on invertebrates were declines in lipid biosynthesis and upregulation of β-oxidation, while vertebrate models suggest increased adipogenesis following treatment with neonicotinoids. Therefore, we hypothesized that there exists synergy between the effects of diet and concurrent exposure to field-realistic concentrations of neonicotinoid insecticides. To address this hypothesis, we fed first instars of the large wolf spider Hogna antelucana with two types of diets and exposed them to field-realistic concentrations of three formulations of neonicotinoids (thiamethoxam, thiacloprid and acetamiprid). We then measured the growth of the tested spiders; the lipid and protein content of their bodies; and their behavior, including ballooning, rappelling, and locomotor parameters. The two tested diets consisted of casein-treated and sucrose-treated Drosophila melanogaster. The dietary treatments affected the lipid and protein content of the spiders, their body weight and carapace length but did not affect any of the measured behavioral parameters. Surprisingly, we did not find any effects of acute exposure to neonicotinoid insecticides on the lipid or protein reserves of spiders. Exposure to neonicotinoids altered the behavior of the spiders as reported previously in other spider species; however, these effects were not affected by dietary treatments. Overall, the dietary treatments did not have any major synergy with acute exposure to field-realistic concentrations of neonicotinoid insecticides.